Emerging antisense oligonucleotide and viral therapies for ALS - Ly, Cindy V. (Curr Opin Neurol, 2018)
PURPOSE OF REVIEW: Amyotrophic lateral sclerosis (ALS) is a rapidly fatal disease for which there is currently no effective therapy. This review describes the current progress of existing molecular therapies in the clinical trial pipeline and highlights promising future antisense oligonucleotide and viral therapeutic strategies for treating ALS. RECENT FINDINGS: The immense progress in the design of clinical trials and generation of ASO therapies directed towards superoxide dismutase-1- (SOD1) and C9orf72 repeat expansion- related disease have been propelled by fundamental work to identify the genetic underpinnings of familial ALS and development of relevant disease models. Preclinical studies have also identified promising targets for sporadic ALS (sALS). Moreover, encouraging results in AAV9-based therapies for spinal muscular atrophy (SMA) provide a roadmap for continued improvement in delivery and design of molecular therapies for ALS. SUMMARY: Advances in preclinical and clinical studies of ASO and viral directed approaches to neuromuscular disease, particularly ALS, indicate that these approaches have high specificity and are relatively safe.